Relationship between optical coherence tomography findings and clinical variables in patients with opiate use disorder - Ozsoy, Filiz; Kulu, Muberra; Ozarslan, Yakup; Korkmaz, Sevda (Consel Brasil Oftalmologia, 2023)
| Purpose: This study aimed to examine optical coherence tomography findings in patients with opiate use disorder by comparing them with healthy controls. Methods: The study included 30 opiate use disorder patients and 30 controls. The participants??? detailed biomicroscopic examinations, visual acuity, intraocular pressure, and both eye examinations were evaluated. A total of 120 eyes were evaluated using optical coherence tomography, measuring the central macular thickness, mean macular thickness, mean macular volume and retinal nerve fiber layer thickness. Moreover, all participants filled in the demographic data form and Barratt Impulsiveness Scale. Results: Upon examination of the optical coherence tomography findings, central macular thickness, mean macular thickness, and mean macular volume were thinner in both eyes in patients with opiate use disorder (p<0.01 in all measurements in both eyes). Similarly, the total values of the superior quadrant and retinal nerve fiber layer thickness were statistically significant in both eyes compared to that in the control group (p=0.007, p=0.002; p=0.049, p=0.007, in the right and left eyes, respectively). Only the left eye was positively correlated with retinal nerve fiber layer superior quadrant measurement and hospitalization (r=0.380, p=0.039). Conclusion: Our results revealed that the patients??? central macular thickness, mean macular thickness, and mean macular volume values were thinner. Increase in the retinal nerve fiber layer thickness superior quadrant thickness and total value was also observed. Further studies with larger sampling groups that evaluate neuroimaging findings should be conducted.
Relação entre os achados da tomografia de coerência óptica e as variáveis clínicas em pacientes com transtorno por uso de opiáceos
Keywords: Opiates alkaloids; Opioid-related disorders; Tomo; graphy; optical coherence; Retinal nerve fiber layer thickness; Macular volume